Heat shucking and cold tumble washing in chlorine-assisted system of green mussel - Ybañez, Cjeshyl Bacusmo; Azanza, Ma. Patricia V. (2002.)
ABSTRACT This study utilized heat shocking and chlorine-assisted tumble washing processing procedures for Perna viridis. The first phase of the study involved the use of steam maintained at 90-95°C for 0-5 min exposure times for heating shocking. Heat shocked and shucked mussel meat was exposed to various chlorine concentrations was water to establish optimum time-temperature protocol for chilled tumble washing procedure. In the Second Phase of the study the shucked and tumble washed mussel meat samples were subjected to physico-chemical and microbiological analyses. It was established that 1 min steaming was the minimum time to necessary effect 100% gaping of green mussel shellstock. Newly heat shocked mussel meat had the following quality profile; 5.93 pH, 0.97 Aw, 4.20 log cfu/g TPC and 2.85 log cfu/g and coliform count. Furthermore, it was observed that a weight gain of about 2% was incurred by the mussel meat samples that were chilled-tumble washed in all the test chlorine concentrations and the time-temperature protocols. Chilled tumble washing of heat shocked mussel meat generally showed a decrease in TPC and coliform count when exposed to 5 and 10 ppm chlorine wash solutions. Increasing the exposure time also generally decreased the microbial counts. Chilling the wash solutions to 5 and 10°C generally showed no effect to the TPC and coliform counts of the tumble washed green mussel meat. This study recommended the use of other modes for heat shocking to further facilitate the ease of shocking. Increasing the chlorine concentration of the wash solution as well as the periods of wash exposure were recommended to increase margin of safety of the product and possibly increase product plumping.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mussels